PENGARUH ISU SOSIOSAINTIFIK DALAM MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI ASAM BASA - Pintaka Kusumaningtyas; Rezky Oktafiani; Mukhamad Nurhadi; Sekar Sulistyaningwarni (Chemistry Education Department of Education and Teaching Faculty, 2020)
The aim of this study was to determine the influence of sosioscientific issues in discovery learning model toward critical thinking skills of students on the subject matter of acid-base. The research method used was quasi experimental, with the type of research design was posttest only control group design. The population in this study was all students of class XI MIPA SMAN 13 Samarinda in the 2018/2019 school year, amounting to 66 students, which were divided into 2 classes. The samples were taken using saturated sampling technique. The technique used to measure critical thinking skills of students was post-test technique in form of essay test. Data were analyzed by normality test, homogeneity test, and independent sample t-test. The results showed the average posttest score in the control class was 72.06 (good category) and the experimental class was 79.36 (good category). Statistical analysis using t-test showed tcount, 3.15 > ttable, 1.66, which means that there was an influence of the use of sosioscientific issues in the discovery learning model toward critical thinking skills of students on the subject matter of acid-base.